Gendered Experiences of Intravenous Iron Infusion Reactions: A Patient Perspective - Roxanna Nasseri Pebdani PhD, CRC, SFHEA (Journal of Patient Experience)
Hypophosphatemia following iron infusion is thought to be a relatively rare complication of intravenous iron infusion, though research is beginning to demonstrate that it occurs more often than previously assumed. Still, healthcare professionals are often unaware of this potential complication. This, coupled with the medical bias women can receive in health settings—plus the over-representation of women receiving intravenous iron—means that symptoms of hypophosphatemia may be misinterpreted or worse, misdiagnosed. This article presents an account of a patient experience of hypophosphatemia following intravenous iron. Key points include: healthcare providers should be aware of this potential complication, healthcare providers must be prepared to listen, assess, address, and treat potential hypophosphatemia that occurs after receiving an iron infusion, and physicians should monitor phosphate, particularly in patients who develop fatigue, nausea, bone pain, and other symptoms of hypophosphatemia after receiving an iron infusion. Further research on the prevalence, impact, and duration of hypophosphatemia following iron infusion is needed.